2021
DOI: 10.3390/app112412129
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Real-Time Online High-Intensity Interval Training on Physiological and Physical Parameters for Abdominally Obese Women: A Randomized Pilot Study

Abstract: Purpose: This study aimed to investigate the effects of online high-intensity interval training (HIIT) in abdominally obese women experiencing health complications due to COVID-19. Methods: Sixteen participants were enrolled and divided into the HIIT group (n = 8) and moderate-intensity continuous training (MICT, n = 8) group. The HIIT group underwent 20 min of exercise consisting of 20 s of high-intensity (85–90% HRmax) exercise followed by 30 s of exercise at 60% HRmax using only body weight. The main exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…In this study, there were significant differences in TC, TG, LDL, and CRP between the PE group and the CON group. These results are consistent with the studies that show that real-time online high-intensity interval training in obese women (BMI > 25 kg/m 2 , and abdominal circumference > 85 cm) reduces visceral fat and LDL during COVID-19 [ 47 ], and is effective in preventing hyperlipidemia and diabetes [ 48 ]. Significant differences in CRP between groups in this study were confirmed and exercise during pregnancy was effective at relieving inflammation, recovering quickly, and reducing the weight of women after childbirth.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, there were significant differences in TC, TG, LDL, and CRP between the PE group and the CON group. These results are consistent with the studies that show that real-time online high-intensity interval training in obese women (BMI > 25 kg/m 2 , and abdominal circumference > 85 cm) reduces visceral fat and LDL during COVID-19 [ 47 ], and is effective in preventing hyperlipidemia and diabetes [ 48 ]. Significant differences in CRP between groups in this study were confirmed and exercise during pregnancy was effective at relieving inflammation, recovering quickly, and reducing the weight of women after childbirth.…”
Section: Discussionsupporting
confidence: 91%
“…In particular, pregnant women, considered as high-risk group with unstable psychological conditions due to changes in hormones, were excluded from vaccination, thereby increasing psychological burdens such as fear of infection and anxiety 3 , 4 ; quarantine also increased the level of physical inactivity and the risk of postpartum depression 5 , 6 . To prevent these problems, maternal care, such as prenatal care, meditation, and exercise, was implemented; however, as all educational programs were suspended after pandemic, women's health was widely threatened 7 .…”
Section: Introductionmentioning
confidence: 99%
“…With growing scientific evidence on the health benefits of physical activity [5,6], many physical activity intervention experiments have emerged [7]. In previous studies, the research participants included adolescents, children, older adults, and patients with specific diseases, whereas outcome variables included mental health, well-being, and physical health [8][9][10][11]. Physical activity intervention research for youth mainly focuses on psychological perspectives, such as self-cognition, emotion, and pressure [12][13][14].…”
Section: Introduction 1physical Activity and Health Benefitsmentioning
confidence: 99%